2D stickman mapping of human physical movements using IMU (sports technology) - Zhang, Chengjie (2018)
In the modern society, sports are playing more and more important roles. The body is the most important carrier of every movement. Every individual has a unique state while executing a physical action. Different movement data including velocity, acceleration and angle can be used to calculate the position and orientation of the human body during exercise. The purpose of the project is to use the data measured by the IMU to establish a real-time stickman model to map physical movements of the lower limbs. The project consists of the design of the hardware system and the programming of the software system. This project uses three joints of the lower extremity as the main research object and uses the IMU to collect movement data of the three joints in daily activities including squatting and jumping and analyze them. Finally, the project uses the Matlab software to establish a real-time stickman model to map the movements of the lower limb. The main innovations and work content of this project can be summarized by the following aspects. a) The previous project of analyzing human movements usually compare and list movement data such as velocity, acceleration and force, which is abstract to reflect the practical different movements. The project establishes an image model to map the physical movements in real time. Any movement of the lower limbs can be observed in real time through the screen. b) Designing and finishing the hardware system is the important foundation of the establishment of the stickman model. Different chips are soldered on the circuit boards to constitute different functional modules. The three identical measuring modules are respectively attached to three joints of the lower limb. The module uses the IMU to measure and collect the motion data of the lower limb, which provide mathematical calculation basis for kinematic equations. The hardware system is also programmed to implement the corresponding function. We use Arduino IDE to upload the programs to different chips c) Converting the motion data into the real-time mapping model is the most critical and difficult part of the project. Based on the dynamic model of the lower limb, we design and establish the stickman model. In the Matlab program, coordinate transformation, rotation matrix method and kinematic equations are used to calculate the position and orientation of the real-time stickman model, which can capture and map the physical movements of the body in real time.